Analisis Proses Konversi dan Kepastian Hukum Sertipikat Hak Milik Tanah Bekas Hak Milik Adat dalam Sengketa Kepemilikan oleh Pihak Lain (Studi Kasus Putusan Mahkamah Agung Nomor 1012 K/Pdt/2023) - Muhammad Zuhdi Alhadiy Siregar; Rosnidar Sembiring; Maria (Jurnal Hukum Lex Generalis, 2025)
The issuance of Freehold Title Certificates (Sertipikat Hak Milik/SHM) for land is intended to provide legal certainty; however, in practice, ownership disputes frequently occur. The issue becomes crucial when involving the conversion of customary land titles (hak milik adat), which in practice has not fully guaranteed legal certainty regarding the history of ownership. This problematic is reflected in Supreme Court Decision No. 1012 K/Pdt/2023. The Supreme Court dismissed the cassation appeal from the heirs (certificate holders) on the grounds that they failed to prove a legal relationship with the original owner, whereas PT. MKP was able to provide evidence of a deed of relinquishment of rights and 20 years of physical possession. The results show, This decision erroneously re-imposes the burden of proving inheritance status on the SHM holder, undermines the negative publication system with a positive tendency, and fails to provide legal protection to the bona fide certificate holder.